Analisis Faktor-Faktor yang Mempengaruhi Kualitas Pelayanan terhadap Kepuasan Pasien - Diana, Sulis; Syahril, Achwan; Anggreni, Dhonna; Wari, Fitria Edni (Institut Penelitian Matematika, Komputer, Keperawatan, Pendidikan dan Ekonomi (IPM2KPE), 2023)
This study aimed to determine the factors that influence service quality on patient satisfaction at Jember Acupuncture House. This research is an analytical survey research with an explanatory approach. The results showed that Data analysis was performed using multiple linear regression tests and the results obtained showed that there was a significant influence between the factors of reliability, responsiveness, and attention. Meanwhile, assurance and appearance factors have no significant effect on patient satisfaction. From this study, the results showed that the overall quality of service at Jember Acupuncture House was good, but some did not show maximum service quality because the services received did not by the expectations and needs of patients.. Keywords: Quality of service, Satisfaction, Patient